2021
DOI: 10.1080/08927022.2021.1880576
|View full text |Cite
|
Sign up to set email alerts
|

In-silico strategies of some selected phytoconstituents from Melissa officinalis as SARS CoV-2 main protease and spike protein (COVID-19) inhibitors

Abstract: Melissa officinalis (Lamiaceae) was used to treat multiple human afflictions. Literary works demonstrated that it has many biological activities. Today’s research aims to recognise Melissa officinalis phyto-derived anti-viral compounds against main protease and spike protein of COVID-19, to gain insight into the molecular interactions. In the current study, 12 molecules taken from Melissa officinalis were analysed through docking, which is derived from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…Residues Asp295 (5.27 Å) and Val104 (4.30 Å) interacted via C-H bond and Pi-sigma, respectively. Five residues including Ile106, Gln110, Thr111, Thr292, and Consistent with previous studies which reported the potential inhibitors of M pro (Park et al, 2015;Aanouz et al, 2020;Bello et al, 2020;Chikhale et al, 2020b;Krupanidhi et al, 2020;Matveeva et al, 2020;Muhammad et al, 2020;Tripathi et al, 2020;Mitra et al, 2021;Prasanth et al, 2021;Varadharajan et al, 2021), in our study, screened four compounds (sesamin, sesaminol, sesamolin, and sesamolinol) were found to be tightly fit into the binding pocket of the M pro of COVID-19.…”
Section: Compoundsupporting
confidence: 91%
“…Residues Asp295 (5.27 Å) and Val104 (4.30 Å) interacted via C-H bond and Pi-sigma, respectively. Five residues including Ile106, Gln110, Thr111, Thr292, and Consistent with previous studies which reported the potential inhibitors of M pro (Park et al, 2015;Aanouz et al, 2020;Bello et al, 2020;Chikhale et al, 2020b;Krupanidhi et al, 2020;Matveeva et al, 2020;Muhammad et al, 2020;Tripathi et al, 2020;Mitra et al, 2021;Prasanth et al, 2021;Varadharajan et al, 2021), in our study, screened four compounds (sesamin, sesaminol, sesamolin, and sesamolinol) were found to be tightly fit into the binding pocket of the M pro of COVID-19.…”
Section: Compoundsupporting
confidence: 91%
“…Some of the studies explained that M pro facilitated the discovery of the antiviral candidate obtained from medicinal plants. [44][45][46][47] Moreover, PL pro was also had been reported as the target to discover the antiviral candidate agents based on the herbal material. [48][49][50][51] On another part, RdRp was also tested as an antiviral target candidate based on a herbal compound reported by Ahmad Mir et al 52 The result of the whole research may be used for support towards the development of the antiviral agent candidate.…”
Section: Resultsmentioning
confidence: 99%
“…The compounds were identified as 2 α ,3 α ,24‐trihydroxyurs‐12‐en‐28‐oic acid ( 1 ), [6] 2 α ,3 α ,24‐trihydroxyolean‐12‐en‐28‐oic acid ( 2 ), [7] 2 α ,3 α ,23‐trihydroxyolean‐12‐en‐28‐oic acid ( 3 ), [8] 2 α ,3 α ,23‐trihydroxyurs‐12‐en‐28‐oic acid ( 4 ), [9] asiatic acid ( 5 ), [10] tormentic acid ( 6 ), [11] arjunolic acid ( 7 ), [12] euscaphic acid ( 8 ), [13] ( Z , E )‐2‐(3,5‐dihydroxyphenyl)ethenyl ester ( 9 ), [14] ( Z , E )‐2‐(3,4‐dihydroxyphenyl)ethenyl ester ( 10 ), [15] Acacetin 7‐ O ‐ β ‐D‐glucopyranosyl‐(1→2)‐[α‐L‐rhamnopyranosyl‐(1→6)]‐ β ‐D‐glucopyranoside ( 11 ), [16] Linarin ( 12 ) [17] . All of them were isolated from MFR for the first time, while 1 – 9 and 11 – 12 were obtained from the genus of Meehania for the first time.…”
Section: Resultsmentioning
confidence: 99%